2008
DOI: 10.1016/j.yexcr.2008.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for the assembly of LINC complexes and their function in cellular mechanical stiffness

Abstract: The evolutionary-conserved interactions between KASH and SUN domain-containing proteins within the perinuclear space establish physical connections, called LINC complexes, between the nucleus and the cytoskeleton. Here, we show that the KASH domains of Nesprins 1, 2 and 3 interact promiscuously with luminal domains of Sun1 and Sun2. These constructs disrupt endogenous LINC complexes as indicated by the displacement of endogenous Nesprins from the nuclear envelope. We also provide evidence that KASH domains mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
295
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 258 publications
(317 citation statements)
references
References 42 publications
17
295
0
Order By: Relevance
“…The addition of amino acids at the Cterminus of the PPPT anchor leads to steric hindrance of PPPT docking into the BI-pocket. These observations are consistent with a previous report showing that an extension of the C-terminal KASH domain sequence prevented the binding to the SUN domain [22][23][24].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The addition of amino acids at the Cterminus of the PPPT anchor leads to steric hindrance of PPPT docking into the BI-pocket. These observations are consistent with a previous report showing that an extension of the C-terminal KASH domain sequence prevented the binding to the SUN domain [22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, we have repeatedly observed that both the SUN domain homotrimer alone and the luminal region of SUN2 containing two coiled-coils and the SUN domain (CC1-CC2-SUN) are sufficient for KASH binding ( Figure 4). However, a truncated form of SUN2 that only contains the second coiled-coil and the SUN domain (CC2-SUN) was not able to bind the KASH peptide, consistent with previous studies [1,10,22,24]. Of note, we previously found that the truncated form containing only CC2 and the SUN domain also showed reduced oligomerization [10].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Traditional fluorescence microscopy focusing on the bottom of the cell suggests that the displacement of these NE proteins caused by lamin depletion does not affect actin filament organization (14). Because the NE distribution of LINC complex proteins is altered in embryonic fibroblasts derived from mice lacking A-type lamins, a model of dilated cardiomyopathy and muscular dystrophy (15,16), we hypothesized that the depletion of lamin A/C from the nucleus would disrupt the organization of the actin cap and the regulation of nuclear shape by cell shape.…”
Section: Resultsmentioning
confidence: 99%